Da cidade ao campo: trajetórias e perspectivas à luz dos acampamentos do MST em Charqueadas - RS - Buzzatti, Mauren (2017)
In view of the change in migration dynamics in Brazil and the influence of this in relation to population movement between rural and urban, this study seeks to understand, in the light of agrarian policy, how the urban population is understood as regards access through the National Agrarian Reform Program, based on a case study, which takes as an indicative source the social profiles of the camped participants in the Movement of Landless Rural Workers (MST), who have been on the margins for four years. highway 401, in the municipality of Charqueadas-RS. In order to do so, it has deepened in a wide bibliographical and documentary research, referring to the different migratory dynamics, in particular the absorption of these to the MST, with the urban-rural logic. The research was also supported by interviews with key informants belonging to the aforementioned Movement, representatives of the National Institute of Colonization and Agrarian Reform (INCRA - RS), as well as with members of the Movement in a situation of encampment, on the grounds that they constitute a demanding contingent by land, and this is the most suitable profile to understand the migratory nuances to the rural, through the governmental incidences. Thus, in terms of the emergence of the urban profile, delimited to the urban-rural migration logic, it was identified, in proportional terms, its manifestation in the late 1990s, in states and regions with the highest demographic density. These subjects compose a profile that, as a rule, does not have a rural link related to land tenure or work associated with it. They are individuals who migrate from the city to the rural for the first time, as a consequence of the socioeconomic dynamics experienced in the urban environment, where the frequent peripheral origin of these individuals is perceived. Once inserted in the middle of search for access to land, they interact with the organizational structure of the MST camps, as well as with the other subjects that are in this space, conforming a relational logic of mutual influences, where they are perceived by their cultural characteristics intrinsic to its urban origin and also perceive this medium from this scope, which highlights singular meanings in the so-called "rural" and "urban" means. Finally, it is highlighted how agrarian policies, since formulated in periods that are not present in the search for land access, and which are still in force, exclude these individuals, mainly through the selective criteria of program participation identified in the questions proof of time of agricultural activity, interviews of agricultural aptitude, as well as in the direction of the policy itself.